KONVERSI PENGGUNAAN BAHAN BAKAR MINYAK (BBM) KE BAHAN BAKAR GAS (BBG) BAGI NELAYAN DI KECAMATAN GALESONG SELATAN KABUPATEN TAKALAR - Mandra, Moh Ahsan S.; -, Sunardi; Paloboran, Marthen (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
The objectives to be achieved in the activities of the CCN-PPM South Galesong inTakalar Regency are: (1) increasing the knowledge and skills to assemble theconverter kit Fuel Gas (BBG), (2) increasing knowledge and skills of performingrepairs and maintenance of the engine (motor) fishing boat, and (3) increasing therevenue generated after the problems of the partners completed. Activity methodsused include: observation, illumination (theory), training (practice), discussion andevaluation. Absorption material mastery by participants on average well and provedat the time of training, 60% can assemble a tool kit with converter good and canserve as the tool converter FUEL to BBG. This training without the constraints ofmeaning and can be carried out in accordance with the expected target. It's just ontraining machine repair, only about 35% to successfully perform diagnosisaccurately, so the majority of trainees are still hard-pressed to find an issue or asource of damage to the machine. This is normal because the machine does requirea lot of practice in other words could not directly fitting just do exercises two orthree times only.